Novel Therapeutics in Sjögren's Disease: A Systematic Literature Review - Bernie (International Medical Journal Corp. Ltd, 2025)
Introduction: Primary Sjögren's syndrome (pSS) is a systemic autoimmune disease with significant morbidity and unmet therapeutic needs. Current treatments are largely palliative. This systematic review synthesizes evidence on novel biologic and immunomodulatory therapies aimed at disease modification. Methods: A systematic search was conducted across multiple databases (PubMed, Semantic Scholar, Springer, etc.) for studies (RCTs, systematic reviews) evaluating novel therapeutics (biologics, immunomodulators) in pSS patients. Data on therapy, population, design, efficacy (ESSDAI, ESSPRI, glandular function), and safety were extracted. Results: Thirty-two studies were included. Agents targeting the CD40/CD40L pathway (iscalimab, dazodalibep) and FcRn (nipocalimab) demonstrated statistically significant and clinically meaningful improvements in systemic disease activity (ESSDAI) and patient-reported symptoms (ESSPRI). In contrast, abatacept, tocilizumab, and JAK/SYK/BTK inhibitors showed limited efficacy. A critical finding was that patients with early disease (≤3 years duration) responded significantly better to biologics. Safety analysis confirmed a higher risk of serious adverse events with biological therapies, though profiles varied by drug class. Glandular function improvements were modest overall but more pronounced with regenerative approaches like stem cell therapy. Discussion: The CD40/CD40L pathway is a validated, high-priority therapeutic target in pSS. Disease duration is a key modifier of treatment response, highlighting a therapeutic window for early intervention. Heterogeneity in trial results is explained by factors including disease duration, dosing, and outcome measurement sensitivity. Conclusion: This review establishes a hierarchy of efficacy, with CD40/CD40L and FcRn blockade as the most promising strategies. Early intervention is crucial for optimal outcomes. Future research must focus on trials in early disease, predictive biomarkers, long-term safety, and regenerative therapies.